2019
DOI: 10.1111/jeb.13435
|View full text |Cite
|
Sign up to set email alerts
|

The effects of male social environment on sperm phenotype and genome integrity

Abstract: Sperm function and quality are primary determinants of male reproductive performance and hence fitness. The presence of rival males has been shown to affect ejaculate and sperm traits in a wide range of taxa. However, male physiological conditions may not only affect sperm phenotypic traits but also their genetic and epigenetic signatures, affecting the fitness of the resulting offspring. We investigated the effects of male‐male competition on sperm quality using TUNEL assays and geometric morphometrics in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 65 publications
3
22
0
Order By: Relevance
“…Moreover, a recent study of zebrafish found that males exposed to rivals had sperm with morphologies that are predicted to promote more efficient fertilization but also had greater levels of DNA damage compared to the sperm of males that were not exposed to rivals, supporting the notion of a trade‐off between male expenditure on gaining fertilizations and on the genetic quality of the offspring they sire (Silva et al. ).…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, a recent study of zebrafish found that males exposed to rivals had sperm with morphologies that are predicted to promote more efficient fertilization but also had greater levels of DNA damage compared to the sperm of males that were not exposed to rivals, supporting the notion of a trade‐off between male expenditure on gaining fertilizations and on the genetic quality of the offspring they sire (Silva et al. ).…”
Section: Discussionmentioning
confidence: 90%
“…The differences in sperm longevity we found among males (indicated by the male effect in the main model, see table 1) may reflect a differential investment according to the male social environment. Earlier studies in the zebrafish showed that sperm traits vary with the intensity of male-male competition and male social status and affect the survival and performance of the resulting offspring (Zajitschek et al 2014;Zajitschek et al 2017), possibly due to the higher mutational load in sperm of stressed males (Silva et al 2019). In addition, longer-lived sperm selected within ejaculates sire embryos with higher survival and adult fitness in zebrafish (Alavioon et al 2019) (Darszon et al 2004) and in several species of externally fertilizing fish (Yanagimachi et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, germline and sperm cells are particularly well protected from oxidative damage in guppies, as suggested by the relatively low senescence rate of ejaculate quality in this species (Gasparini, Devigili, & Pilastro, 2019). However, in the zebrafish Danio rerio , a high male–male competition environment leads males to produce faster swimming sperm, at a cost of DNA integrity and offspring fitness (Silva et al., 2019; Zajitschek, Hotzy, Zajitschek, & Immler, 2014), suggesting that this protection is incomplete. To distinguish between these alternative explanations, it would be necessary to experimentally manipulate male courtship effort independently from sperm priming.…”
Section: Discussionmentioning
confidence: 99%